ANALYSIS OF FEEDING DIFFICULTY RISK FACTORS IN CHILDREN AGED 24-36 MONTHS (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
Feeding difficulty was a condition where the child was unable to eat and refuses certain foods. Feeding difficulties in children could be caused by organic factors related to health problems in children and non-organic factors related to nutritional factors and psychosocial factors. This study aimed to analyze non-organic risk factors including history of exclusive breastfeeding, time of initiation of complementary feeding, history of complementary feeding 6-24 months, pattern of child feeding as a cause of feeding difficulties in children aged 24-36 months. The research was conducted in Banyumanik Village with 39 respondents. This research method was an observational analytic study with a cross-sectional approach with a consecutive sampling method. Data regarding exclusive breastfeeding, time of initiation of complementary feeding, history of complementary feeding, pattern of child feeding, and children's eating difficulties were obtained from interviews with mothers who had children aged 24-36 months. Data analysis was performed using the chi-square statistical test. The results showed that there was no significant relationship between exclusive breastfeeding and the time at which complementary foods were given and the incidence of feeding difficulties in children aged 24-36 months (p=0.653, p=0.457) and there was a significant relationship between history of complementary foods and feeding patterns. with the incidence of eating difficulties in children aged 24-36 months (p=0.03, p=0.000). Giving complementary foods that were not suitable could cause difficulty eating in children. Provision of appropriate MPASI could help children in the process of learning to eat and getting used to good eating habits in children. Eating behavior that was not in accordance with the basic feeding rules caused eating difficulties in children. Data analysis was performed using the chi-square statistical test.
Keywords: feeding difficulty; psychosocial factors; nutritional factors